Changes in histidine decarboxylase expression influence extramedullary hematopoiesis in postnatal mice. Issue 5 (28th October 2020) - Otsuka, Hirotada; Endo, Yasuo; Ohtsu, Hiroshi; Inoue, Satoshi; Kuraoka, Mutsuki; Koh, Miki; Yagi, Hideki; Nakamura, Masanori; Soeta, Satoshi
Abstract: Histidine decarboxylase (HDC), histamine synthase, is expressed in hematopoietic stem cells and in lineage‐committed progenitors in the bone marrow (BM). However, the role of histamine in hematopoiesis is not well described. To evaluate the role of histamine in hematopoiesis, we analyzed the changes in HDC expression at hematopoietic sites, the BM, spleen, and liver of 2‐, 3‐, and 6‐week‐old wild‐type mice. We also performed morphological analyses of the hematopoietic sites using HDC‐deficient (HDC‐KO) mice. In wild‐type adults, HDC expression in the BM was higher than that in the spleen and liver and showed an age‐dependent increase. Histological analysis showed no significant change in the adult BM and spleen of HDC‐KO mice compared to wild‐type mice. In the liver, HDC expression was temporarily increased at 3 weeks and decreased at 6 weeks of age. Morphological analysis of the liver revealed more numerous hematopoietic colonies and megakaryocytes in HDC‐KO mice compared to wild‐type mice at 2 and 3 weeks of age, whereas no changes were observed in adults. Most of these hematopoietic colonies consisted of B220‐positive B‐lymphocytes and TER119‐positive erythroblasts and were positive for the cell proliferation marker PCNA. Notably, these hematopoietic colonies declined in HDC‐KO mice upon N‐acetyl histamine treatment. A significant increase in the expression of hematopoiesis‐related cytokines, Il3, Il7, Epo, Gcsf, and Cxcl12 mRNA was observed in the liver of 3‐week‐old HDC‐KO mice compared to wild‐type mice. These results suggest that histamine‐deficiency may maintain an microenvironment suitable for hematopoiesis by regulating hematopoiesis‐related cytokine expression in the liver of postnatal mice.